2019
DOI: 10.1155/2019/9203057
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Promotes Strawberry Fruit Ripening and Affects Ripening-Related Processes

Abstract: Strawberry is a typical nonclimacteric fruit, whose ripening mechanism needs to be further investigated. Sucrose has been recently proved as a signal molecule, participating in strawberry fruit ripening and related processes. While in the effects of sucrose application timing and concentration on ripening, fruit qualities remain unclear, as well as the transcriptome-wide details about the effects of sucrose on the gene expression involved in ripening-related processes. In this study, strawberry fruits at the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Nevertheless, it is worth noting that in the absence of ABA, sucrose treatment had no effect on the expression of FaNCED , even if it was able to significantly upregulated the expression of FaBG. Taken together, these data suggest that sucrose level can modulate ABA content in strawberry fruit ( Luo et al., 2019 ).…”
Section: Sugar Signaling In Fruit Development and Ripening And Its Crmentioning
confidence: 58%
See 4 more Smart Citations
“…Nevertheless, it is worth noting that in the absence of ABA, sucrose treatment had no effect on the expression of FaNCED , even if it was able to significantly upregulated the expression of FaBG. Taken together, these data suggest that sucrose level can modulate ABA content in strawberry fruit ( Luo et al., 2019 ).…”
Section: Sugar Signaling In Fruit Development and Ripening And Its Crmentioning
confidence: 58%
“…As a consequence of this observation, this sugar has been proposed to induce the expression of key genes involved in ABA biosynthetic pathway, such as 9-cis-epoxycarotenid dioxygenase ( NCED ) and beta-glucosidase ( BG ) ( Jia et al., 2013 ). A recent investigation confirmed that ABA (95 µM) and sucrose (100 µM) treatments resulted in the overexpression of FaNCED1 and FaNCED2 in sprayed strawberry fruit ( Luo et al., 2019 ). Nevertheless, it is worth noting that in the absence of ABA, sucrose treatment had no effect on the expression of FaNCED , even if it was able to significantly upregulated the expression of FaBG.…”
Section: Sugar Signaling In Fruit Development and Ripening And Its Crmentioning
confidence: 84%
See 3 more Smart Citations